Three-dimensional bioprinting collagen/silk fibroin scaffold combined with neural stem cells promotes nerve regeneration after spinal cord injury - Jiang, Ji-Peng; Liu, Xiao-Yin; Zhao, Fei; Zhu, Xiang; Li, Xiao-Yin; Niu, Xue-Gang; Yao, Zi-Tong; Dai, Chen; Xu, Hui-You; Ma, Ke; Chen, Xu-Yi; Zhang, Sai (Neural regeneration research, 2020)
Many studies have shown that bio-scaffolds have important value for promoting axonal regeneration of injured spinal cord. Indeed, cell transplantation and bio-scaffold implantation are considered to be effective methods for neural regeneration. This study was designed to fabricate a type of three-dimensional collagen/silk fibroin scaffold (3D-CF) with cavities that simulate the anatomy of normal spinal cord. This scaffold allows cell growth in vitro and in vivo. To observe the effects of combined transplantation of neural stem cells (NSCs) and 3D-CF on the repair of spinal cord injury. Forty Sprague-Dawley rats were divided into four groups: sham (only laminectomy was performed), spinal cord injury (transection injury of T10 spinal cord without any transplantation), 3D-CF (3D scaffold was transplanted into the local injured cavity), and 3D-CF + NSCs (3D scaffold co-cultured with NSCs was transplanted into the local injured cavity. Neuroelectrophysiology, imaging, hematoxylin-eosin staining, argentaffin staining, immunofluorescence staining, and western blot assay were performed. Apart from the sham group, neurological scores were significantly higher in the 3D-CF + NSCs group compared with other groups. Moreover, latency of the 3D-CF + NSCs group was significantly reduced, while the amplitude was significantly increased in motor evoked potential tests. The results of magnetic resonance imaging and diffusion tensor imaging showed that both spinal cord continuity and the filling of injury cavity were the best in the 3D-CF + NSCs group. Moreover, regenerative axons were abundant and glial scarring was reduced in the 3D-CF + NSCs group compared with other groups. These results confirm that implantation of 3D-CF combined with NSCs can promote the repair of injured spinal cord. This study was approved by the Institutional Animal Care and Use Committee of People's Armed Police Force Medical Center in 2017 (approval No. 2017-0007.2).